The inhibitory effect of tachyplesin I on thrombosis and its mechanisms. (12th June 2019) - Li, Huimin; Liu, Bin; Wu, Jun; Yu, Huajun; Huang, Hui; Chen, Xi; Chen, Baoan; Wu, Shang; Ma, Jingyao; Liu, Wen; Chen, Xiaoyi; Lan, Liubo; et al.
Abstract: Thrombotic diseases are major cause of cardiovascular diseases. This study was designed to investigate the effect of tachyplesin I on platelet aggregation and thrombosis. Platelet aggregation was analysed with a whole blood aggregometer. The mice were employed to investigate the effect of tachyplesin I on thrombosis in vivo. Tachyplesin I inhibited thrombin‐induced platelet aggregation in a dose‐dependent manner. Furthermore, tachyplesin I significantly reduced thrombosis in carrageenan‐induced tail thrombosis model by intraperitoneal injection (0.1, 0.2 or 0.4 mg/kg) or intragastric administration (15, 30 or 60 mg/kg). Tachyplesin I also prolonged the bleeding time (BT) and clotting time (CT). The results revealed that tachyplesin I inhibited platelet aggregation and thrombosis by interfering the PI3K/AKT pathway. Tachyplesin I did not show significantly toxicity to mice under 300 mg/kg via intravenous injection. The results show that tachyplesin I inhibits thrombosis and has low toxicity. It is suggested that tachyplesin I has the potential to develop a new anti‐thrombotic drug. Abstract : Tachyplesin I significantly inhibits platelet aggregation to prevent thrombosis. Tachyplesin I inhibits platelet aggregation by affecting the PI3KIAKT. Tachyplesin I is a new potential anti‐thrombotic peptide.